Mechanical Properties and Machinability of Glass Fiber-Reinforced Polyetheretherketone - Ji, S.J.; Yu, H.J.; Zhao, J.; Liang, F.S. (Проблемы прочности, 2015)
Polyetheretherketone (PEEK) is a new type of special engineering plastic that has broad market potentials due to its particular microstructure and mechanical properties. However, few data can be found in the literatures devoted to the mechanical properties and machinability of PEEK, especially in the superprecision field. For the first time, the microscopic mechanical properties and machinability of glassfiber-reinforced PEEK (GF/PEEK), which is one typical derivative of pure PEEK, are studied. The nanoindentation experiment was performed to analyze the microscopic mechanical properties of GF/PEEK. The machinability was studied by single-point diamond turning (SPDT) on the GF/PEEK surface, the roughness and form accuracy of the machined surface were obtained in the following test. Experimental results indicate that GF/PEEK has good microscopic mechanical properties and machinability. Полиэфирэфиркетон новый вид специального конструкционного пластика, который благодаря особой микроструктуре и механическим свойствам имеет большие возможности выхода на рынок. Однако в литературе можно найти не так много данных, относящихся к механическим свойствам и обрабатываемости полиэфирэфиркетона, особенно в сверхточной области. Впервые проведено исследование обрабатываемости и механических свойств на микроскопическом уровне полиэфирэфиркетона, упрочненного стекловолокном, который является типичным производным чистого полиэфирэфиркетона. Выполнено наноиндентирование с целью анализа механических свойств материала на микроскопическом уровне. Обрабатываемость материала изучали с помощью одноточечной алмазной обточки по его поверхности, при испытании были получены значения шероховатости и точности формы обработанной поверхности. Экспериментальные результаты свидетельствуют о хороших механических свойствах и обрабатываемости полиэфирэфиркетона, упрочненного стекловолокном.